2016
DOI: 10.1111/php.12583
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Regeneration of ATP Level after Irradiation in Human Skin Fibroblasts by Coenzyme Q10

Abstract: Human skin is exposed to a number of harmful agents of which the ultraviolet (UV) component of solar radiation is most important. UV-induced damages include direct DNA lesions as well as oxidative damage in DNA, proteins and lipids caused by reactive oxygen species (ROS). Being the main site of ROS generation in the cell, mitochondria are particularly affected by photostress. The resulting mitochondrial dysfunction may have negative effects on many essential cellular processes. To counteract these effects, coe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 32 publications
0
13
0
1
Order By: Relevance
“…The human body synthesizes CoQ10 to produce cellular energy in mitochondria and to protect cells from the deleterious effects of free radicals [28,29]. The role of oxidative stress in the skin aging process has indeed been well recognized [3,30].…”
Section: Discussionmentioning
confidence: 99%
“…The human body synthesizes CoQ10 to produce cellular energy in mitochondria and to protect cells from the deleterious effects of free radicals [28,29]. The role of oxidative stress in the skin aging process has indeed been well recognized [3,30].…”
Section: Discussionmentioning
confidence: 99%
“…Photo-stressed skin benefitted from CoQ10 application on account of reduction in in situ free radical levels. Schniertshauer et al 112 further showed that CoQ10 could restore ATP production, prevent mitophagy, and alleviate oxidative stress in aged skin cells. Nicotinamide, also known as Vitamin B3 or niacinamide, is the precursor of NAD+, which is required for mitochondrial ATP production.…”
Section: Mitochondrial Targeting For Skin Regenerationmentioning
confidence: 99%
“…Subsequent studies reported during the 2000s demonstrated multiple benefits of coenzyme Q 10 in both animal models and human skin, which included skin anti-aging properties and, through supplementation, a potential treatment for psoriasis [ 139 , 140 , 141 , 142 ]. Additionally, more recent studies from 2015 through 2018 validated the: (a) antioxidant effects of coenzyme Q 10 to support and maintain cellular energy levels in human keratinocytes [ 143 , 144 ], (b) accelerated regeneration of ATP levels after irradiation in human fibroblasts [ 144 , 145 ], and (c) the safety and effective delivery of coenzyme Q 10 into the epidermis to improved human skin health [ 143 , 144 , 145 ].…”
Section: Coenzyme Q 10mentioning
confidence: 99%